Throughfall drop size distributions: a review and prospectus for future research. (9th May 2017) - Levia, Delphis F.; Hudson, Sean A.; Llorens, Pilar; Nanko, Kazuki
Abstract : Throughfall is the dominant input of water to forests. Throughfall drop size and the distribution thereof are important because of their influence on the forest water balance, soil erosion, and, possibly, biogeochemical cycling. However, our inadequate understanding of throughfall drop size distributions has hampered progress in the identification of direct and indirect linkages between throughfall inputs and the biogeochemistry and physiological ecology of forests. This review provides a snapshot of our current understanding of throughfall drop size distributions by tracing the historical development of throughfall drop size studies and examining the determinants of throughfall drop size. The theory and methods of drop size studies also are reviewed to consolidate our collective knowledge of throughfall drop size distributions to date. Some of the gaps in our current knowledge, among many, include: (1) the effects of snowmelt on throughfall drop size; (2) the role and extent to which different canopy phenophases affect throughfall drop size; and (3) the extent to which throughfall drop size affects the chemistry of and biogeochemical cycling within forest soils. Closing these knowledge gaps will likely lead to the better conceptualization of rainfall partitioning processes and more definitive linkages between the cause‐and‐effect relationships between throughfall and soil erosion, forest biogeochemistry, and plant physiological ecology, for example. WIREs Water 2017, 4:e1225. doi: 10.1002/wat2.1225 This article is categorized under: Science of Water > Hydrological Processes Abstract : Differential drop size distributions for rainfall and throughfall.